ANALISIS PEMASARAN JERUK SIAM (CITRUS NOBILIS LOUR VAR) DI DESA KUOK KECAMAATAN KUOK KABUPATEN KAMPAR - Arjuna Hasudungan; Ermi Tety; Eliza Eliza (Indonesian Journal of Agricultural Economics, 2020)
The purpose of this research was to analyze the marketing of Siamese citrus in Kuok Village based on market performance. The location of research is determined purposively, that is the village which become the center of citrus production. Method of sampling farmer by simple random sampling. Determination of sample marketing agency using snowball sampling method by following the marketing channel. To analyze the data used marketing cost analysis, marketing margin, marketing advantage, marketing efficiency, farmer's share and profit to cost ratio.The results show that there are three marketing channels of citrus, namely the marketing channel of I farmers - collector traders - Grade A, Grade B and Grade C), marketing channel II farmers to retailers and marketing channels III farmers sell directly to end consumers. The analysis of market performance shows that the most efficient channels, seen from the calculation of marketing costs, marketing margins, marketing advantages, marketing efficiency, farmer's share and profit-to-cost ratio are on channel II.